2010
DOI: 10.1271/bbb.100327
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a Novel Fucoidan-Degrading Microorganism

Abstract: A bacterium utilizing fucoidan from the brown alga Cladosiphon okamuranus as sole carbon source was isolated and identified as Flavobacterium sp. F-31. The strain produced intracellular enzymes involved in fucoidan degradation and desulfation, but desulfation activity was not detected until the molecular weight of fucoidan fell to less than several tens of thousands due to enzymatic degradation. Only fucoidan proved to be an inducible substance for the production of the degrading enzymes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…F31, 11) but separation of strain F31 cells from the culture broth by centrifugation was extremely problematical, because strain F31 appeared to produce viscous substances. Besides strain F31, we isolated bacteria showing an ability to grow in media containing fucoidan as sole carbon source.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…F31, 11) but separation of strain F31 cells from the culture broth by centrifugation was extremely problematical, because strain F31 appeared to produce viscous substances. Besides strain F31, we isolated bacteria showing an ability to grow in media containing fucoidan as sole carbon source.…”
Section: )mentioning
confidence: 99%
“…F31, degrading the fucoidan of C. okamuranus, and found that the strain had intracellular enzymes desulfating fucoidan, besides lowering its molecular weight. 11) In addition, no desulfation activity was detected until the molecular weight of fucoidan was decreased to less than several tens of thousand by enzymatic degradation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The preparation of obtained clones followed purification of recombinant DNA was carried out as described previously [Lin et al, 2009;Ohshiro et al, 2010;Rattanachomsri et al, 2011]. Escherichia coli DH5á and recombinant E. coli were cultured in LB containing 50 μg/mL ampicillin at 37 o C. Sequencing was performed with an ABI Prism BigDye Terminator Cycle Sequencing Ready Kit (Applied Biosystems, Foster City, CA) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Lfucanase is an example of endofucoidanase obtained from F. algae, which can produce fuco-oligosaccharides with immunomodulatory activity. Exofucoidanases act on the non-reducing end of sulfated fucose residues to produce oligomers and reduce the molecular weight at a relatively slower rate (Berteau and Mulloy, 2003;Ohshiro et al, 2010;Silchenko et al, 2013).…”
Section: In Vitro Enzymatic Degradation Of Marine Sulfated Polysacchamentioning
confidence: 99%